संस्कृति स्रोतस्विनी : शिप्रा - Kripashankar Vyas (Madhya Pradesh Hindi Granth Academy, 2011)
The book discusses the cultural and religious significance of the river Shipra.
Sanskriti Srotaswini : Shipra
Keywords: संस्कृति स्रोतस्विनी : शिप्रा; Sanskriti Srotaswini : Shipra; Culture; Hindi; Hindi